Perceived impacts of climate change in pastoralist regions of Ethiopia: A qualitative study applying the concept of One Health - Tamire, M.; Mor, Siobhan M.; Baylis, M.; Kaba, M. (MDPI, 2025)
Ethiopia is highly vulnerable to the effects of climate change, with the increasing geographic extent, intensity, and frequency of drought. This study aimed to examine how pastoralist communities understand climate change and its impacts. We conducted a qualitative study among pastoral communities in Ethiopia using focus group discussions with community representatives and key informant interviews with human and animal health and agriculture experts. The collected data were analyzed using qualitative content analysis. Participants viewed deforestation and population growth as the main causes of climate change. They found that climate change caused high temperatures, a shortage of rainfall, and drought. These changes affected the environment, food security, and animal health, impacting their livelihoods, health, and social systems. Coping strategies included engaging in new economic activities, environmental recovery attempts, migration, and seeking food aid for survival. They suggested providing food aid, improving access to human and animal health care, and implementing early warning systems at the community level. The pastoralists perceived that climate change destroyed the natural environment, increased food insecurity, and negatively affected social systems and health. Collaborative actions are needed to mitigate these effects, initiate local environmental adaptation mechanisms, enhance water and food security, and improve animal and human health services.